“Uma lúgubre página”: experiências suicidas no Maranhão (1834- 1888) - FERREIRA , Carlos Victor de Sousa (2020)
The present study focuses on the analysis of the experiences and representations about the suicides of the enslaved that occurred in Maranhão between 1834-1888. Therefore, extensive bibliographic and documentary research was necessary, in journals, medical theses, police records, correspondence between authorities, death certificates, police inquiries and bodies of law: civil, ecclesiastical and criminal. To understand the hundreds of suicides that occurred in the period, this study had a qualitative and quantitative analysis. The intercrossing of the documentation allowed us to infer several evidences about the experiences of these subjects before their suicides. In the serial analysis we present the cases in graphs and tables, this helped us to understand the “profiles” of the practitioners, as well as to highlight the main motivations, the most used methods and the times of greatest occurrences. The juridical condition of the suicide, whether free or slave, presented new evidence that was presented in this study, that is why we understand suicides from the experiences of these subjects in their daily lives and the roles they probably assumed socially. The motivations that contributed to the decision to shorten their lives say a lot about the society of 19th century Maranhão and about the conceptions of death and dying.